Perspectives of Undergraduate and Graduate Students on Utilizing ChatGPT: Analyzing Its Role in Question Preparation - Özer, Ece Ceren; Benzer, Semra; Benzer, Recep (Science Insights Education Frontiers, 2025)
Artificial intelligence (AI) is increasingly integrated into daily life across various sectors such as banking, healthcare, tourism, and education. This research aims to investigate science teacher candidates’ opinions on using ChatGPT in education and their approaches to preparing questions with this artificial intelligence tool. Specifically, it aims to elucidate the role of ChatGPT in question preparation processes and its potential applications in education. A case study methodology was employed, focusing on 17 fourth-year science teacher candidates and 6 graduate students in a science education master’s program during the fall semester of 2023-2024. Data were collected using an interview form and images of participants’ conversations with ChatGPT. Content analysis of the data reveals that most participants intend to use ChatGPT in their teaching process for research and question creation. Participants provided specific details in their prompts to ChatGPT, including grade level, unit, subject area, learning outcomes, question type, number, and difficulty level. This study highlights the potential of ChatGPT to enhance educational practices and support teachers in personalizing learning experiences.